Peninggalan Sejarah Kota Ternate Sebagai Sumber Belajar di SMA Mafakati Kecamatan Pulau Hiri - Zulkifli Zulkifli; Firman Amir (Jurnal Ilmiah Wahana Pendidikan, 2022)
History is evidence of events that occurred in the past and to reconstruct through history learning, the students of SMA Mafakati, Hiri Island District. So, through historical heritage in Ternate City, it is used as a learning resource which is one of the new innovations in history subjects at the high school level, with the aim that students are motivated to participate in the teaching and learning process directly through visits to historical sites in Ternate City. From the results of the study that the reality of history lessons is a boring subject for students because the problem is that so far the history teacher in delivering history material is only centered on books, to change the concept of history learning, the role of the history teacher is needed so that all historical relics in Terenate City are used as learning resources for history subjects with the aim that the teaching and learning process can be achieved properly. History subjects have various sources, and from these sources students not only get knowledge from books owned by history teachers but utilize historical relics in Ternate City as a very effective learning resource for students to know about events that occurred in Ternate City, in detail.